La novela histórica de ayer a hoy La tierra del fuego como prototipo ilustre - Paulino, Jacinta Magdalena Mejía, 1968- (2017)
Abstract This study, conducted to complete the degree of MA in Spanish from the University of Iceland, seeks to investigate the current status of the Historical Novel as a literary genre through the analysis of the novel La tierra del fuego (1998), by the Argentinian novelist Sylvia Iparraguirre. The main objective of the investigation is to provide an overview of the theoretical approaches and the current standing of this genre and its sub-genre by identifying its origin, characteristics and principal elements. Subsequently, an analysis of their literary classification is presented, to determine the possible need to reconsider the Historical Novel as a sub-genre of the Novel, or if instead it should be considered as a relevant literary genre on its own accord. Furthermore, a review of both sub-genres, the Historical Novel and the socalled New Historical Novel, is offered in order to consider the possibility of merging them into one category, or if those should be maintained separate. To conduct the study the literary narrative La tierra del fuego (Ísl. Eldlandið), first published in Buenos Aires in 1998, is used as an example of a Historical Novel. In the first part of the study a theoretical background is established, whilst in the second part the theory is applied to the analysis of the novel in order to obtain answers to the research questions presented. To that aim, this research project revisits the Historical Novel and the New Historical Novel as literary categories and suggests their renewed categorization within the literary genre and contemporary Latin American literature. Key concepts: Latin American Literature, Historical Novel, New Historical Novel. Resumen En el estudio aquí presentado, conducido para completar los estudios de maestría de la Universidad de Islandia, se tiene como propósito investigar el desarrollo y el estado actual de la novela histórica como género literario, por medio del análisis de la novela La tierra del fuego (1998), de la escritora argentina Sylvia Iparraguirre. El ...